Implementasi Metode Analytical Hierarchy Process (AHP) pada Rancang Bangun Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Pada PT XYZ - Nur Elah; Rakhmat Sudrajat (PINTER : Jurnal Pendidikan Teknik Informatika dan Komputer, 2025)
The diverse performance of employees at PT XYZ has an impact on the quality of the company. The main objective of this research is to develop a High-Achieving Employee Decision-Making System to help improve employee motivation and performance. The system implements a method to weight predetermined criteria, namely the Analytical Hierarchy Process (AHP) method, which helps assess employees based on these criteria. In its development, the PHP programming language was used as the scripting language, MySQL as the database type, and XAMPP as the web server. The system development approach used the waterfall method, supported by an environment model, behavioural model, and implementation model, which were illustrated through Context Diagrams, Data Flow Diagrams, ERDs, and relational databases. Blackbox testing was used as a method of testing the system in the final stage. Testing results indicate that the system is 100% compliant and operates according to the created test scenarios.